Finite-Time Output Feedback Attitude Tracking Control for Rigid Spacecraft - Zou, An-Min (IEEE transactions on control systems technology, 2014)
This brief investigates the finite-time output feedback attitude control of a rigid spacecraft. First, a nonlinear observer is designed. Through geometric homogeneity and Lyapunov theories, it is shown that the proposed observer can achieve the semiglobal finite-time stability. Then, a finite-time output feedback controller is proposed based on the finite-time observer. Rigorous proof shows that the proposed control law ensures semiglobal stability and guarantees the attitude of a rigid spacecraft to track a time-varying reference attitude in finite time. Simulation results are presented to illustrate the performance of the proposed controller.